Some Fading-related Problems at Shortwave Propagation Path in the Baltics - Lossmann, E.; Madar, U.; Raja, A.; Meister, M. A. (Elektronika ir Elektrotechnika, 2008)
The ionospheric propagation of shortwave frequencies is characterized by stochastic fluctuations, known as fading. Due to fading effects, the level of radio signal can vary (tens to hundreds of times), but in addition, the same phenomenon can cause a randomly variable temporal dropouts – from tenths of a second to tens of seconds. Within this paper, the fading characteristics of the broadcast transmitter signal from Pori (Finnish Broadcast Company, YLE) over two medium-range propagation paths in northern Estonia and northern Latvia are examined. Comparisons are drawn for both groundwave and ionospheric propagation data. Observed fading phenomenon is described with reference temporal and frequency aspects. The research data is statistically analyzed in MATLAB environment and the graphical results are presented. Ill. 9, bibl. 10 (in English; summaries in English, Russian and Lithuanian).